Cardiac Function Assessment in Fetuses With Ductus Arteriosus Constriction: A Two-Dimensional Echocardiography and FetalHQ Study - Ma, Jing; Cao, Haiyan; Hong, Liu; Liu, Juanjuan; Song, Xiaoyan; Shi, Jiawei; Zhang, Yi; Cui, Li; Zhang, Li; Xie, Mingxing (Frontiers in Cardiovascular Medicine, 2022)
Background: Fetal ductal constriction (DC) is associated with excessive polyphenols food (PRF) consumption during pregnancy. However, the effect of this hemodynamic change on fetal cardiac function still needs to be elucidated. Therefore, this study aimed to evaluate the cardiac function of fetuses with PRF related DC and to describe serial observations of cardiac function changes. Methods: We compared the traditional echocardiographic indices including morphological, hemodynamic, and functional parameters between study fetuses and controls. For global and segmental deformation analysis of left and right ventricles, Fetal HQ with the speckle-tracking technique was used to calculate SI, GLS, FS, FAC, etc. In addition, follow-up data were compared with a generalized linear model. Results: A total of 60 DC fetuses and 60 gestational-matched controls were enrolled in our study, with 20 DC fetuses undertaking a follow-up echocardiogram after 2~3 weeks. Compared with controls, there was a distinct decrease in RVGLS (-13.39±3.77 vs -21.59±2.51, p<0.001), RVFAC (22.20±9.56 vs 36.01±4.84, p<0.001), LVGLS (-19.52±3.24 vs -23.81±2.01 p<0.001) and LVFAC (39.64±7.32 vs 44.89±4.91, p=0.004). For 24-segment FS analysis, DC fetuses showed lower FS in left ventricular (LV) segments 18 to 24, with no difference in LV segments 1 to 17. Right ventricular (RV) FS in segments 4 to 23 was also reduced in the DC group. 24-segment SI analysis indicated significantly lower SI in DC than those in controls for LV segments 1 to 14, and RV segments 19 to 24. We found pulsatility index (PI) of DA was an independent variable for RVGLS (β=-0.3129, p=0.04). In 20 DC fetuses with follow-up echocardiograms, no obvious difference in myocardial deformation was found between initial examination and follow-up data. Conclusion: Left and right ventricular performance were both impaired in DC fetuses, along with a series of morphological and hemodynamic changes. Although the state of DA constriction improved on second examinations, cardiac function was not completely restored.